Metabolomic exploration of the effects of habituation to livestock trailer and extended transportation in goats - Batchu, Phaneendra; Naldurtiker, Aditya; Kouakou, Brou; Terrill, Thomas H.; McCommon, George W.; Kannan, Govind (Frontiers in Molecular Biosciences, 2022)
Goats raised for meat production are often transported long distances. Twelve-month-old male Spanish goats were used to determine the effects of habituation to trailers on plasma metabolomic profiles when transported for extended periods. In a split-plot design, 168 goats were separated into two treatment (TRT; whole plot) groups and maintained on two different paddocks. Concentrate supplement was fed to one group inside two livestock trailers (habituated group, H), while the other group received the same quantity of concentrate, but not inside the trailers (non-habituated, NH). Goats were subjected to a 10-h transportation stress in 4 replicates (n = 21 goats/replicate/TRT) after 4 weeks of habituation period. Blood samples were collected prior to loading, 20 min after loading (0 h), and at 2, 4, 6, 8, and 10 h of transportation (Time; subplot). A targeted quantitative metabolomics approach was employed to analyze the samples. The data were analyzed using R software and MIXED procedures in SAS. Several amino acids (alanine, serine, glycine, histidine, glutamate, trans-hydroxyproline, asparagine, threonine, methylhistidine, ornithine, proline, leucine, tryptophan) were higher (p < 0.05) in the H group compared to the NH group. Six long-chain acylcarnitines were higher (p < 0.05), while free (C0) and short-chain (C3, C5) carnitines were lower (p < 0.05) in the NH goats compared to the H goats. In general, amino acid concentrations decreased and long-chain acylcarnitine (>C10) levels increased with transportation time (p < 0.05). Butyric acid, α-ketoglutaric acid, and α-aminoadipic acid concentrations were lower (p < 0.05) and β-hydroxybutyric acid concentrations were higher in the NH goats compared to the H goats. Plasma glucose, non-esterified fatty acid (NEFA) and urea nitrogen concentrations were significantly influenced by Time (p < 0.01). Plasma NEFA concentrations were significantly lower (p < 0.01) in the H group than the NH group. Habituation to trailers can be beneficial in enhancing stress coping abilities in goats due to higher concentrations of metabolites such as butyrate and certain amino acids that support antioxidant activities and immune function. Plasma long-chain acylcarnitines may be good indicators of stress during long-distance transportation in goats.